PBS - MacNeil/Lehrer NewsHour: Cost of War
A PBS TV program presented by Jim Lehrer and Robert MacNeil about the inflation and degrading economic situation in Serbia. The program features interviews with locals who describe the living conditions in the war-torn country and their means of survival.